Assessment of specificity of immunologic tests for detection of tuberculosis infection in children with juvenile idiopathic arthritis - Aksenova, V. A.; Dementyeva, E. K.; Kazakov, A. V.; Klevno, N. I.; Snovskaya, M. A.; Zhuzhula, A. A.; Alyabieva, N. M.; Kudlay, D. A. (Medicinskij sovet, 2024)
Introduction. The use of genetic engineering biological agents (GEBA) in the treatment of rheumatic diseases over the past decades has led to a significant improvement in the prognosis in this group of patients. However, against the background of anti-tumor necrosis factor α therapy (anti TNF- α ), the risk of developing tuberculosis increases tenfold. Aim. To evaluate the specificity and safety of Mantoux test, recombinant tuberculosis allergen (RTA) test, IGRA tests: TB-Feron IGRA, T-SPOT.TB, QuantiFERON-TB GIT in patients from 5 to 18 years of age, who are at risk for the development of tuberculosis, due to the use of immunosuppressive therapy, including GEBP. Materials and methods. This clinical trial is a prospective single-center open-label study with 120 patients under observation. Girls predominated among the patients – 71 (59.2%), the average age was 12 years (95% CI [5.2–17.4]). As part of the treatment of the underlying disease, patients in the vast majority of cases (78.3%) received iFNO- α drugs: etanercept (67 people), adalimumab (25 people), golimumab (2 people). Results and discussion. According to the results of a comprehensive medical examination, including CT scan of the chest organs, the presence of active tuberculosis was not established in any of the patients. A positive result of the RTA sample was registered in 0.8% of the subjects, Mantoux test in 46.6%, T-SPOT.TB – 1.7%, TB-Feron IGRA and QuantiFERON-TB GIT – 0.8% each. During the safety assessment, it was noted that within 28 days after the study, none of the 120 patients had any adverse events. Patients need appropriate screening before starting treatment and regular follow-up examinations. Conclusions. The Mantoux test with 2 TE has low specificity (0.49), and the sample with RTA (0.99), TB-Feron IGRA (0.99), T-SPOT.TB (0.98) and QuantiFERON-TB GIT (0.99) are highly specific and safe as tests for detecting tuberculosis infection in children with juvenile idiopathic arthritis.